Effect of White, Red, Blue Light and Darkness on IAA, GA and Cytokinin Induced Stomatal Movement and Transpiration - Journal, IMR (International Multidisciplinary Research Journal, 2014)
Plant growth regulators are the signaling molecules which control physiological as well as metabolic functions starting from seed germination to flowering and senescence. Along with this, light of different wavelengths also play an important role in the life span of plants starting from photosynthesis to transpiration. In this work we tried to find out the effect of plant growth regulators along with lights of various wavelengths on stomatal movement and transpiration rate. In this study we try to observe the influence of auxin, gibberellin, cytokinin in Piper betel L. under blue light, red light, white light and darkness in stomatal regulation. it was found that, red light inhibited transpiration rate and stomatal opening in auxin and gibberellin treated leaves although it accelerated cytokinin treated stomatal opening.